STRATEGI PENGEMBANGAN OBJEK WISATA DESA TENGANAN PEGRINGSINGAN KABUPATEN KARANGASEM - Anak Agung Gede Wijaya (Jurnal Ilmiah Hospitality Management, 2014)
The purpose of this research is to examine the readiness Tenganan Pegringsingan village as the village tourism object, physically and non-physically, examine the strategy and suitable improvement model to be excellent village tourism object and pro village people. Purposive Sampling is used for the research method, and the respondent are the tourists and the elder of the society. To collect the data. It’s used observation, structural interview, and documentary. To analyze the data, it’s used SWOT analysis method. The result of the research shows the potency of tourism which is owned by the village as agricultural tourism and cultural tourism. But the facilities and infrastructural tourism in the village are not complete enough for the readiness of tourism object. That’s why to improve it. It needs strategy by building physic and non-physic facilities. To be an ideal village tourism object which can compete with other tourism objects, so it needs strategy to build the physic and non-physic facilities.